Analysis Of Perfume Seed Inventory Control At PT. Perintis Kiprah Sampono (Case Study Of Aromania Perfumery Karawang) - Suci Nurrohimmah, Meyta; Ludiya, Eka; Dwiana Ratnamurni, Elis (Publisher Cv. Inara, 2023)
This study aims to analyze the inventory control of perfume seeds at PT. Pioneer Gait Sampono (case study of aromania perfumery Karawang). The aim is to find out how far the inventory control of aromania perfume seeds has been running effectively and efficiently. The method used in this research is descriptive with a qualitative approach, using a purposive sampling technique. Data collection techniques by conducting observations, interviews and documentation, to test the validity and reliability by using a triangulation process including source triangulation, technical triangulation, and time triangulation. The results of this study indicate that there are constraints on the supply of perfume seeds, where consumer demand is not fulfilled due to empty supplies resulting in lost sales or disruption of the sales process at the company, but with the always better control analysis method used, it can control every good inventory starting from the process. ordering, receiving goods, checking goods, storing goods, the process of releasing goods, the lead time of goods arriving to the safety stock.